Coalition politics among opposition parties in Malaysia : a case study of Pakatan Rakyat (2008-2016) - Nur Atika Binti Hairi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study examines the internal politics in Pakatan Rakyat (PR) component political parties (i.e. PKR, PAS and DAP) as the coalition opposition parties in Malaysia from 2008 to 2015. The PR was the first coalition of opposition parties in Malaysia that managed to deny Barisan Nasional of their two thirds majority in the 2008 general elections and won the popular vote in the 2013 general elections. This study is based on the assumption that there was a linkage between PR's strength and contributions and various challenges that the PR faced. Political conflicts that constrained the coalition stability in PR leading to its dissolution are investigated. The study employs Arend Lijphart's theory of consociational democracy as a framework for the analysis. The study argues that the PR as the opposition coalition in Malaysia was stronger than Barisan Alternatif (BA) or Pakatan Harapan (PH). The study found that hudud issues were the main factors that led to the dissolution of PR. However, it was also found that the main unifying element that kept the parties together in PR was main leader in politics, Anwar Ibrahim. Given the findings of this study, to achieve better electoral results, opposition coalitions in Malaysia would need to work out a better strategy to accommodate component parties with diverse ideological positions.